Engineering secure software and systems : 8th International Symposium, ESSoS 2016, London, UK, April 6-8, 2016. Proceedings /: 8th International Symposium, ESSoS 2016, London, UK, April 6-8, 2016. Proceedings. (2016) - Unknown
No abstract available